Work readiness scale for pharmacy interns and graduates: A cross-sectional study - Safa S. Almarzoky Abuhussain; Mahmoud E. Elrggal; Abdulaziz K. Salamatullah; Assma A. Althobaity; Amal F. Alotaibi; Tahani M. Almeleebia; Thamer A. Almangour; Abdullah A. Alhifany (Elsevier, 2021)
Introduction: As the number of unemployment among pharmacy graduates increases, the Saudi Ministry of Labor implemented extra measures to facilitate their training and hiring by the private sectors. Nevertheless, there is a paucity of data regarding pharmacy graduates' work readiness (WR). Hence, we aim to assess their WR and identify predicting factors associated with WR among pharmacy graduates' in Saudi Arabia. Methods: A 46-item self-reported pre-validated anonymous work readiness scale (WRS) survey with a 5-point Likert scale was administered to pharmacy senior students and graduates using Qualtrics XM® survey tool over the month of May 2020. The main outcome was to assess WRS for pharmacy interns and graduates and identify factors associated with work readiness. Results: A total of 617 participants have participated in this survey, out of which 46.5% were freshly graduated pharmacists and 19.6% were pharmacy interns. Most participants (82.3%) were PharmD candidates or graduates. Around two-third of participants (63%) have successfully completed all survey items. The maximum points scored was 223 out of 230, and the median overall score was found to be 175. There was no significant association with gender, age, or type of university regarding overall scores. However, a statistically significant odds ratio was observed with PharmD program type and previous pharmaceutical marketing training (OR = 1.778, 95% CI = 1.143-2.765: OR = 0.618, 95% CI = 0.432-0.884, respectively). Conclusion: The overall median score shows a good work readiness level among pharmacy students/graduates in Saudi Arabia; however, PharmD program graduates exposed to advance pharmacy training, including the pharmaceutical marketing experience, have higher work readiness odds than Bpharm graduates. Further studies involving other related perspectives, such as stakeholders, employers, and preceptors, would give a clear image of pharmacy graduates' job readiness levels.